Aging and pensions in general equilibrium: Labor market imperfections matter - David de la Croix; Olivier Pierrard; Henri R. Sneessens (Institute for the Study of Labor (IZA), 2010)
This paper re-examines the effects of population aging and pension reforms in an OLG model with labor market frictions. The most important feature brought about by labor market frictions is the connection between the interest rate and the unemployment rate. Exogenous shocks (such as aging) leading to lower interest rates also imply lower equilibrium unemployment rates, because lower capital costs stimulate labor demand and induce firms to advertize more vacancies. These effects may be reinforced by increases in the participation rate of older workers, induced by the higher wage rates and the larger probability of finding a job. These results imply that neglecting labor market frictions and employment rate changes may seriously bias the evaluation of pension reforms when they have an impact on the equilibrium interest rate.
Keywords: E24; H55; J26; J64; 330; overlapping generations; search unemployment; labor force participation; aging; pensions; labor market